ANALISA VALUE CREATION PADA PERGURUAN TINGGI SWASTA DI SURABAYA BERDASARKAN PERSEPSI MAHASISWA JURUSAN TEKNIK INDUSTRI - Pambudi, Larissa (Business Accounting Review, 2013)
The competition in the education world, especially in university, is getting tougher as value creation has to given by the university to the students to stand still in the current competition. This research objective was to find out whether there was a different level of value creation based on gender, GPA and seniority of 135 industrial engineering students in five private universities which are offering high tuition fees. From the Analysis of Variance (ANOVA), it was concluded that there was significant difference of value creation given by the University to the students based on gender, and there was no significant difference of value creation given by the University to the students based on GPA and seniority.